The Role of Islamic Religious Education in Forming Sakinah Families - Septian, Rahmat Yudhi; Hiptraspa, Zepri (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2023)
Abstrak: Keluarga sakinah adalah suatu gambaran keluarga yang harmonis dan ideal, ditandai dengan rumah tangga yang dihiasi oleh pribadi-pribadi salih secara spiritual dan terpenuhinya kebutuhan pokok berupa sandang, pangan dan papan. Kehidupan suami istri adalah rumus dari kebahagiaan dunia. Menciptakan hidup bahagia di keluarga, secara otomatis kebahagiaan dunia dan akhirat akan tercapai bersama. Salah satu faktor penting untuk menciptakan keluarga sakinah adalah pendidikan agama Islam. Tujuan karya ilmiah ini adalah untuk mengetahui peran pendidikan agama Islam dalam membentuk kelurga sakinah. Adapun metode penelitian yang digunakan adalah library research. Hasil penelitian menunjukkan bahwa keluarga sakinah akan terbangun dengan memilih pasangan hidup, rumah tangga yang dilandasi cinta, ketenangan dalam rumah tangga, membagun rumah tangga yang baik dan pendidikan agama Islam memiliki andil besar dalam membangun keluarga sakinahAbstract: A sakinah family is an image of a harmonious and ideal family, marked by a household adorned with spiritually righteous individuals and the fulfillment of basic needs in the form of clothing, food and shelter. Husband and wife life is the formula of world happiness. Creating a happy life in the family, automatically the happiness of the world and the hereafter will be achieved together. One important factor for creating a sakinah family is Islamic religious education. The purpose of this scientific work is to find out the role of Islamic religious education in forming a sakinah family. The research method used is library research. The results of the study show that a sakinah family will be built by choosing a life partner, a household based on love, calm in the household, building a good household and Islamic religious education has a big contribution in building a sakinah family